Effectiveness and safety of botulinum toxin in comparison with surgery for drooling in paediatric patients with neurological disorders: a systematic review. Issue 5 (June 2022) - Silva, J.P.S.; Faria, L.V.; Almeida, R.C.; Medeiros, Y.L.; Guimarães, L.D.A.
Abstract: Different therapeutic methods for chronic drooling in paediatric patients with neurological problems have been described in the scientific literature. However, there is no consensus on the ideal strategy of treatment. The aim of this study was to compare botulinum toxin injection therapy and surgical modalities to control drooling in paediatric patients with neurological disorders. A systematic literature search was conducted on nine electronic databases for publications until April 2020. Six articles were included with a total sample of 209 patients, 67.4% (n = 141) of whom had cerebral palsy. All studies used injections of botulinum toxin type A with application to the submandibular and/or parotid salivary glands. The surgical treatments were duct ligation in the parotid and/or submandibular salivary glands, duct relocation in the submandibular salivary glands, and glandular excision of the submandibular and sublingual salivary glands. There were complications in only 16.1% (n = 27) of the sample (11 cases due to botulinum toxin application and 16 due to surgery). Drooling control was assessed by objective and subjective measures. Although surgical procedures presented a higher risk of adverse effects than botulinum toxin type A in all the studies and measurements performed, they presented larger and longer-lasting positive effects on drooling. We suggest bilateral submandibular duct relocation with bilateral sublingual gland excision or isolated bilateral submandibular duct ligation, which were the surgical techniques with the largest samples in this review. Nevertheless, further studies are necessary to compare samples with botulinum toxin type A and surgical treatment.